2015
DOI: 10.1007/s13197-015-1933-x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antioxidant properties of wild mushrooms Boletus edulis and Xerocomus badius prepared for consumption

Abstract: Wild edible mushrooms Boletus edulis and Xerocomus badius were prepared for consumption by braising with 10 % canola oil (half of the batch was blanched prior to braising). Fresh X.badius had comparable to B.edulis amounts of proximate components and higher levels of most B-group vitamins and antioxidants. Analyzed mushrooms prepared for consumption fulfilled 7-14 % RDA of vitamin B1 for healthy adults and 15-35, 18-37 and 1 % RDA of B2, B3 and B3 respectively. Prepared for consumption mushrooms were rich in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Preferable TPC and antioxidant activities of BD and BM were also similar to other Boletus species as previous studies. [3,4,11,[16][17][18] This study was revealed a lack of anticancer activities of BD and BM (maximum concentration = 100 µg/ml) against KB, MCF7, NCI-H187, HepG2 and CaCO 2 cell lines, and no cytotoxicity to normal cell also (Vero and HDFn cells). Anticancer activity of Boletus species was reported in literature review, however, its activity via immunmodulation and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Preferable TPC and antioxidant activities of BD and BM were also similar to other Boletus species as previous studies. [3,4,11,[16][17][18] This study was revealed a lack of anticancer activities of BD and BM (maximum concentration = 100 µg/ml) against KB, MCF7, NCI-H187, HepG2 and CaCO 2 cell lines, and no cytotoxicity to normal cell also (Vero and HDFn cells). Anticancer activity of Boletus species was reported in literature review, however, its activity via immunmodulation and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 85%
“…[16] They may also have strong antioxidant activity. [3,4,11,17,18] Boletus griseipurpureus Corner 1972 (Boletaceae) is a wild edible ectomycorrhizal mushroom, [19][20][21] rich in protein and low in fat. Thai local name is called "Hed Sa med," characterized by (1) Macroscopic features included pileus 3.0-6.0 cm across, convex to plane, gray to purple or light purple, surface covered with gray black short soft hairs when young; fresh white and firm when young, later softer, unchanging when injured; tube small and firm, pallid white when young, later pinkish to pale brown; and stipe 3.0-6.0 cm long, 1.5-3.0 cm across, purple, cylindrical to clavate, increasing in thickness to clavate toward the base, sometime with pale brown net at the apex.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant activities displayed by S. himantioides are even higher than those found in other in vitro studies of fungi (Cordyceps) exposed to UV radiation (45,46). Antioxidant properties of other Boletales fungi have been investigated in previous reports, but not under in vitro conditions (47)(48)(49)(50)(51). Melanin and carotenoid derivatives are a family of compounds with strong antioxidant activity (52).…”
Section: Discussionmentioning
confidence: 99%
“…The highest values for B. regius extract (13.42 mg Fe/g dw) can be explained by their high level of phenolic compounds in comparison with other analysed mushrooms. Jaworska et al [26] determined the antioxidant activity of edible mushrooms, including B. edulis. Our result for B. edulis is in accordance with the value obtained in the mentioned paper.…”
Section: Total Reducing Power (Trp) Assaymentioning
confidence: 99%